2017
DOI: 10.1097/acm.0000000000001491
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Student Interest in Teaching Through a Medical Student Teaching Competition

Abstract: Problem Clinician educators have realized the value not only of assigning teaching roles to medical students but also of offering explicit training in how to teach effectively. Despite this interest in the development of medical students’ teaching skills, formal teaching instruction and opportunities for practice are lacking. Approach To encourage medical student interest in teaching, the authors developed and implemented a medical student teaching competition (MSTC) at Emory University School of Medicine du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…From this study, it is very obvious that most staff members came from the non-innovative curriculum with significant response 0.05, yet they make use of attending and participating in FDAP, which indicates its usefulness in providing chances for learning new skills, as proved by other studies [26][27][28]. The study observed that 84% of the faculty members are interested in the presentation, which is in agreement with other studies [29,30], while 86% consider it as enriching their experience as teaching staff, which add a lot of skills to them, in finding that it is confirmed by other authorities (31). Despite the heavy work and follow-up on our presentation, the rate of positive perception of the staff to the topics is covers all medical domains, the outcomes as in any other studies might be explained by having innovative curriculum and perhaps the staff experience of assessing the presentations is well developed since the college started functioning FDAP three years ago.…”
Section: Discussionsupporting
confidence: 88%
“…From this study, it is very obvious that most staff members came from the non-innovative curriculum with significant response 0.05, yet they make use of attending and participating in FDAP, which indicates its usefulness in providing chances for learning new skills, as proved by other studies [26][27][28]. The study observed that 84% of the faculty members are interested in the presentation, which is in agreement with other studies [29,30], while 86% consider it as enriching their experience as teaching staff, which add a lot of skills to them, in finding that it is confirmed by other authorities (31). Despite the heavy work and follow-up on our presentation, the rate of positive perception of the staff to the topics is covers all medical domains, the outcomes as in any other studies might be explained by having innovative curriculum and perhaps the staff experience of assessing the presentations is well developed since the college started functioning FDAP three years ago.…”
Section: Discussionsupporting
confidence: 88%
“…Advantages of this approach include the ability to adapt quickly to shifts in context, content and learner needs [ 8 ]. To date, the BST model has been implemented in the postgraduate and undergraduate curricula at our institution [ 12 , 13 ] and other institutions including the Massachusetts General Hospital, Boston University, and Medical College of Wisconsin. (Kerri Palamara McGrath, MD, email communication, October 2020; Gopal Yadavalli, MD, e-mail communication, February 2018; Marty Muniz, MD, and Pat Foy, MD, e-mail communication, June 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Potential advantages of bite-size learning in health professions education include its ability to contend with cognitive load and ability to use this approach in concert other instructional strategies [ 5 ]. Early reports suggest this approach is feasible and viewed positively by learners in postgraduate and undergraduate medical education [ 12 , 13 ]. To date, literature is largely limited to descriptive report with limited exposure and outcomes reported [ 9 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Survey questions for section entitled “Student satisfaction with Existing Career Development Offerings” were adapted from Zink et al [ 6 ] and are listed in their entirety in Supplementary materials . The items in the section “Student agreement with Career Expectations” were adapted from DeSimone et al [ 9 ]. Open-ended questions were generated by the authors and vetted by a peer-audience for evaluation of purpose, wording, and intent of each survey item and revised as necessary to improve audience understanding and optimize item quality and reliability.…”
Section: Activitymentioning
confidence: 99%